2023
DOI: 10.3389/fcvm.2023.1023394
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants, pathophysiological pathways, and oral anticoagulation in patients with hypertrophic cardiomyopathy and atrial fibrillation

Abstract: Atrial fibrillation (AF) is commonly prevalent in patients with hypertrophic cardiomyopathy (HCM). However, whether the prevalence and incidence of AF are different between genotype-positive vs. genotype-negative patients with HCM remains controversial. Recent evidence has indicated that AF is often the first presentation of genetic HCM patients in the absence of a cardiomyopathy phenotype, implying the importance of genetic testing in this population with early-onset AF. However, the association of the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Although there is a dearth of studies directly addressing stroke prevention in HOCM patients without confirmed persistent AFib, some research has explored the potential benefits of anticoagulation in patients with cardiomyopathies, including HOCM, without persistent AFib [ 2 ]. SPAF1 study demonstrated that aspirin and warfarin were both effective agents in reducing ischemic stroke and systemic embolic events in patients with Afib when compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although there is a dearth of studies directly addressing stroke prevention in HOCM patients without confirmed persistent AFib, some research has explored the potential benefits of anticoagulation in patients with cardiomyopathies, including HOCM, without persistent AFib [ 2 ]. SPAF1 study demonstrated that aspirin and warfarin were both effective agents in reducing ischemic stroke and systemic embolic events in patients with Afib when compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Potential underdiagnosis of arrhythmias: It is possible that arrhythmias, including AFib, are underdiagnosed in HOCM patients without persistent AFib. Using loop recorders or prolonged monitoring may detect intermittent arrhythmias that could contribute to stroke risk [ 2 ]. Therefore, not relying solely on confirmed persistent AFib diagnosis may be crucial in identifying underlying arrhythmias and managing stroke risk effectively in HOCM patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations